Upaya Pemberdayaan Apotek Hidup Dan Pentingnya Tanaman Obat Dalam Menjaga Imunitas Tubuh Selama Pandemi Covid-19 - Jihan Sasmita Reza; Maysarah Binti Bakri (Jurnal Riset dan Pengabdian Masyarakat, 2022)
The Covid-19 pandemic delays learning activities on campus, especially in the process of practicum, student community service (KPM), and completing final assignments. Not only students, the pandemic also has an impact on the society. This condition requires the society to be healthy for doing daily activities. One way to do it is by consuming healthy and natural food such as vegetables or herbals. The objectives of this study were (1) to identify the types of to improve the health status of society, (2) to find out the way of using herbals in the program and the benefit of it as raw materials for herbal medicine as an alternative of chemical drugs. The KPM student initiates to make a living pharmacy to improve the body’s immune system. The students performs Covid-19 prevention socialization and train the village community of Doy, in the cultivation of herbs to maintain the immunity. The expected result of such activities is increasing society’s interest in growing a living pharmacy plant in their yard, increasing society knowledge in optimizing their garden for the cultivation of living pharmacies, and increasing public knowledge regarding the advantages of each herbal plant